2019
DOI: 10.1177/1078087419839492
|View full text |Cite
|
Sign up to set email alerts
|

Does Inter-Municipal Cooperation Really Reduce Delivery Costs? An Empirical Evaluation of the Role of Scale Economies, Transaction Costs, and Governance Arrangements

Abstract: Inter-municipal cooperation in public service delivery has attracted the interest of local authorities seeking to reform public service provision. Cost saving, together with better quality and coordination, has been among the most important drivers of such cooperation. However, the empirical results on inter-municipal cooperation and its associated costs offer divergent outcomes. By conducting a meta-regression analysis, we seek to explain this discrepancy. We formulate several hypotheses regarding scale econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 97 publications
0
47
0
Order By: Relevance
“…Principal-agent problems intensify when multiple stakeholders (in joint type 2 and 3 ALBs) are involved in service delivery. Such joint service delivery, that can take place through for example inter-municipal bodies or institutional publicprivate partnerships (Bel and Sebo 2018;Blaeschke and Haug 2018;Cäker and Nyland 2017;Carini, Giacomini, and Teodori 2019;Soukopová and Vaceková 2018;Sørensen 2007;Van Thiel 2017, 2019b) can potentially induce conflicts in governance and monitoring. For example, local governments can face free-riding problems or duplication in monitoring if there is no agreement on which principal will be in charge of monitoring, which can cause inefficiency.…”
Section: Multiple Principalsmentioning
confidence: 99%
“…Principal-agent problems intensify when multiple stakeholders (in joint type 2 and 3 ALBs) are involved in service delivery. Such joint service delivery, that can take place through for example inter-municipal bodies or institutional publicprivate partnerships (Bel and Sebo 2018;Blaeschke and Haug 2018;Cäker and Nyland 2017;Carini, Giacomini, and Teodori 2019;Soukopová and Vaceková 2018;Sørensen 2007;Van Thiel 2017, 2019b) can potentially induce conflicts in governance and monitoring. For example, local governments can face free-riding problems or duplication in monitoring if there is no agreement on which principal will be in charge of monitoring, which can cause inefficiency.…”
Section: Multiple Principalsmentioning
confidence: 99%
“…Studies of this issue are also available for the Czech Republic, namely a study focused on differences between types of IMC institutional arrangements [ 25 ], a study focused on the limits of public–private partnerships and contracting out [ 26 ], or a study focused on competition and efficiency in MSWM services [ 27 ], which again concluded that small municipalities in particular benefit from participating in IMC. A recent metaregression analysis of evidence on IMC benefits in public service provision supports this as well [ 23 ].…”
Section: Introductionmentioning
confidence: 78%
“…However, there is no unified perspective on the benefits of IMC, and mixed results have also been reported [ 21 , 22 ] with no clear consensus [ 23 ]. This observed inconsistency is supported by an analysis of the effects of IMC regarding the costs of 12 common local government services conducted using data from New York State [ 1 ], where some of the services showed decreased costs, some did not show any difference in costs, and some even showed an increase in costs.…”
Section: Introductionmentioning
confidence: 99%
“…However, if entities gain legal autonomy, the direct connection to the democratic governance chain is replaced by indirect governance through owner assemblies and corporate boards, thus increasing the authority-operator distance and making border crossing more formal. This is especially true if they have two or more owners, causing inter-owner coordination formalities and problems and impairing individual owners' governance control (Voorn, Van Genugten, and Van Thiel 2019;Bel and Sebö 2018;Blåka 2017;Sørensen 2007). Finally, outsourcing service-provision to entities owned by private or other public authorities (ownership autonomy) will increase the distance further, often implying control through formal contracts (Bel and Warner 2008;Ohemeng and Grant 2008;Bel and Costas 2006).…”
Section: Conceptual Framingmentioning
confidence: 99%